DAKWAH DAN ISLAM FUNDAMENTALIS - Sudir Koadhi (TASÂMUH, 2018)
The term fundamentalism was initially used only to refer to Catholics who rejected modernity and maintained the teachings of religious orthodoxy. However, at present, the term is also used for adherents of other religions which have similarities so there are also Islamic, Hindu and Buddhist fundamentalism. Over time, the use of the term fundamentalism raises certain images, such as extremism, fanaticism, or even terrorism in maintaining religious beliefs. The Islamic fundamentalist movement in Indonesia is more influenced by domestic and foreign social-political instability, from the Dutch colonial era until the end of the Suharto government. The era of reform, freedom of opinion and groups, is a moment for fundamentalists to voice their opinions, offer solutions to overcome the multidimensional crisis that occurred in Indonesia. Therefore, the propaganda of wisdom, advice, and dialogue must continue to be established with the fundamental groups of Islam to straighten out some of them have come out of the rules of Amar makruf nahimungkar. Advice and dialogue must continue to be made for them to improve the shortcomings